Nifedipine induced gingival enlargement in an edentulous patient: a case report with one year follow up - Shaik Mohammed Asif; Naheeda Shaik; Bhavna Barthunia; Sultan Mohammed Kaleem; M Zakirulla; Mohammed Zahir Kota; Fawaz Abdul Hamid Baig (BMC, 2018)
Abstract Background Gingival enlargement due to calcium channel blockers is a common complaint reported by patients. It can be localized or generalized and can range from mild to severe, affecting patients appearance and function. Nifedipine induced gingival enlargement is noticed only in 10 % of patients and very few cases of Nifedipine induced gingival enlargement in an edentulous patient have been documented in the literature. Case presentation Here in, we report a case of gingival enlargement in a 70 year old hypertensive edentulous patient who was on low dose Nifedipine therapy. Patient wanted complete dentures. We planned to excise the overgrowth and followed up for 1 year. Conclusion Nifedipine induced gingival enlargement noticed only in 10 % of patients. Hence, there is a need for physicians and dentist to make a coordinated treatment plan and practice care while prescribing these drugs which are associated with gingival overgrowth.